Analisis Kebutuhan Pengembangan Media Activity Book untuk Meningkatkan Kemandirian Mengurus Diri Sendiri - asturiyah asturiyah (JURNAL PENA EDUKASI, 2023)
Abstract: This research is motivated by the independence of kindergarten children aged 4-5 years who have not yet developed optimally. This research aims to determine the needs of kindergarten children aged 4-5 years regarding the development of activity book media to train independence in taking care of themselves. The approach used in this research is quantitative. The samples taken for this research were kindergarten children aged 4-5 years at TKIT Nurul Qomar Semarang using an observation sheet instrument. The observation data was then analyzed using percentage techniques. The research results show that more than 50% have not shown the development of independence to take care of themselves according to expectations. This means that many students still appear to be starting to develop, and there are even students who have not yet developed their independence in taking care of themselves. Thus, it is necessary to develop activity book media in the hope of developing and training the independence of kindergarten children aged 4-5 years in taking care of themselves. Keywords: Activity Book; independence; self. Abstrak: Penelitian ini dilatarbelakangi oleh kemandirian anak TK usia 4-5 tahun yang belum berkembang dengan maksimal. Penelitian ini bertujuan untuk mengetahui kebutuhan anak TK usia 4-5 tahun mengenai pengembangan media activity book untuk melatih kemandirian mengurus diri sendiri. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif. Sampel yang diambil untuk penelitian ini yaitu anak TK usia 4-5 tahun di TKIT Nurul Qomar Semarang dengan menggunakan instrumen lembar observasi. Data hasil observasi kemudian dianalisis menggunakan teknik persentase. Hasil penelitian menunjukkan lebih dari 50% belum menunjukkan perkembangan kemandirian mengurus sendiri sesuai harapan. Artinya, sebagian besar anak didik masih terlihat mulai berkembang bahkan masih ada anak didik yang belum berkembang kemandiriannya dalam mengurus diri sendiri. Dengan demikian, diperlukan pengembangan media activity book dengan harapan dapat mengembangkan dan melatih kemandirian anak TK usia 4-5 tahun dalam mengurus dirinya sendirKata kunci: Activity Book; diri sendiri; kemandirian.